Knowledge and Awareness of Congenital Cytomegalovirus Among Women - Jiyeon Jeon; Marcia Victor; Stuart P. Adler; Abigail Arwady; Gail Demmler; Karen Fowler; Johanna Goldfarb; Harry Keyserling; Mehran Massoudi; Kristin Richards; Stephanie A. S. Staras; Michael J. Cannon (Hindawi Limited, 2006)
Background. Congenital cytomegalovirus (CMV) infection is a leading cause of disabilities in children, yet the general public appears to have little awareness of CMV. Methods. Women were surveyed about newborn infections at 7 different geographic locations. Results. Of the 643 women surveyed, 142 (22%) had heard of congenital CMV. Awareness increased with increasing levels of education (P<.0001). Women who had worked as a healthcare professional had a higher prevalence of awareness of CMV than had other women (56% versus 16%, P <.0001). Women who were aware of CMV were most likely to have heard about it from a healthcare provider (54%), but most could not correctly identify modes of CMV transmission or prevention. Among common causes of birth defects and childhood illnesses, women's awareness of CMV ranked last. Conclusion. Despite its large public health burden, few women had heard of congenital CMV, and even fewer were aware of prevention strategies.